2014
DOI: 10.18632/oncotarget.2140
|View full text |Cite
|
Sign up to set email alerts
|

Usp5 links suppression of p53 and FAS levels in melanoma to the BRAF pathway

Abstract: Usp5 is a deubiquitinase (DUB) previously shown to regulate unanchored polyubiquitin (Ub) chains, p53 transcriptional activity and double-strand DNA repair. In BRAF mutant melanoma cells, Usp5 activity was suppressed by BRAF inhibitor (vemurafenib) in sensitive but not in acquired or intrinsically resistant cells. Usp5 knockdown overcame acquired vemurafenib resistance and sensitized BRAF and NRAS mutant melanoma cells to apoptosis initiated by MEK inhibitor, cytokines or DNA-damaging agents. Knockdown and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 39 publications
9
46
0
Order By: Relevance
“…11 Although some improvement was achieved in selectivity, we were unable to fully modify DUB selectivity with G9 because we retained Usp5 inhibition, which was previously noted as a WP1130 target. 10,22 However, Usp5 was activated in myeloma cells, and its inhibition increases p53 accumulation, as we have shown in this study and as others have shown in their studies and in other tumor types. 10,22,28 Because p53 is infrequently inactivated by mutation in B-cell tumors, it remains a potential effector of apoptosis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…11 Although some improvement was achieved in selectivity, we were unable to fully modify DUB selectivity with G9 because we retained Usp5 inhibition, which was previously noted as a WP1130 target. 10,22 However, Usp5 was activated in myeloma cells, and its inhibition increases p53 accumulation, as we have shown in this study and as others have shown in their studies and in other tumor types. 10,22,28 Because p53 is infrequently inactivated by mutation in B-cell tumors, it remains a potential effector of apoptosis.…”
Section: Discussionsupporting
confidence: 84%
“…10,22 However, Usp5 was activated in myeloma cells, and its inhibition increases p53 accumulation, as we have shown in this study and as others have shown in their studies and in other tumor types. 10,22,28 Because p53 is infrequently inactivated by mutation in B-cell tumors, it remains a potential effector of apoptosis. Therefore, G9-mediated inhibition of Usp5 and p53 accumulation may amplify the effects of Usp9x/Usp24 inhibition in some tumors rather than pose a disadvantage as a result of partial selection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, different DUBs may target the same substrate, providing a multi-facet regulation or a cell-context dependent regulation. Until now, USP5 has been shown to link two carcinomas: alterations of USP5 isoforms in glioblastoma tumorigenesis and USP5 linked-suppression of p53 in melanoma [25,26]. Treatment of DUBs inhibitor EOAI3402143, targeting to USP9X and USP5, succeed to suppress melanoma growth [26].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, USP5 has been shown to link two carcinomas: alterations of USP5 isoforms in glioblastoma tumorigenesis and USP5 linked-suppression of p53 in melanoma [25,26]. Treatment of DUBs inhibitor EOAI3402143, targeting to USP9X and USP5, succeed to suppress melanoma growth [26]. Thus, DUBs could be the important targets for disease therapy [27].…”
Section: Discussionmentioning
confidence: 99%